Acute Intestinal Obstruction: A Rare Aetiology. (26th June 2012) - Chatterjee, Shamita; Chatterjee, Souvik; Kumar, Sanjeev; Gupta, Shahana
Abstract : Internal herniation of small intestine is a very rare entity, and it poses a real diagnostic challenge clinically. Recurrent entrapment of the bowel may lead to partial to complete intestinal obstruction and eventually strangulation of the small bowel. Of this rare clinical entity, left paraduodenal hernia is more common. High index of suspicion with prompt management may prevent bowel strangulation and gangrene. We present a case of acute intestinal obstruction due to left paraduodenal hernia with malrotation of midgut in a 55-year-old male patient.